2018
DOI: 10.1101/376228
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Bed nucleus of the stria terminalis regulates fear to unpredictable threat signals

Abstract: The bed nucleus of the stria terminalis (BNST) has been implicated in conditioned fear and anxiety, but the specific factors that engage the BNST in defensive behaviors are unclear. Here we examined whether the BNST mediates freezing to conditioned stimuli (CSs) that poorly predict the onset of aversive unconditioned stimuli (USs) in rats. Reversible inactivation of the BNST selectively reduced freezing to CSs that poorly signaled US onset (e.g., a backward CS that followed the US), but did not eliminate freez… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 180 publications
4
42
0
Order By: Relevance
“…Two subsequent decades of work have improved this perhaps oversimplified distinction between amygdala versus BNST mediating fear versus anxiety. The BNST has since been identified as an important mediator of the limbic forebrain processes that encode aversive motivational states, specifically ambiguous or temporally unpredictable aversive cues (Davis et al 2010, Daldrup et al 2016, Goode and Maren, 2017, Naaz et al 2019, Goode et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Two subsequent decades of work have improved this perhaps oversimplified distinction between amygdala versus BNST mediating fear versus anxiety. The BNST has since been identified as an important mediator of the limbic forebrain processes that encode aversive motivational states, specifically ambiguous or temporally unpredictable aversive cues (Davis et al 2010, Daldrup et al 2016, Goode and Maren, 2017, Naaz et al 2019, Goode et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, BNST did not affect acute fear responses (exhibited either during conditioning or recall), supporting that predictable CS-induced fear expression is not dependent on BNST activity (Goode et al, 2019;Sullivan et al, 2004). However, it had significant impact on fear memory formation that subsequently manifested in enhanced fear levels.…”
Section: Chemogenetic Activation Of Bnst Facilitates Fear Learning Bmentioning
confidence: 58%
“…Early studies investigating the rodent BNST observed functional division between the amygdala and BNST, which was supported by human fMRI data. According to this model, amygdala mediates imminent phasic 'fear-like' states, whereas BNST mediates more diffuse unconditioned 'anxiety-like' states (Daniel and Rainnie, 2016;Davis et al, 2010;Goode et al, 2019). Recently, accumulating evidence showed that both amygdala and BNST are recruited under both phasic and sustained (or conditioned and unconditioned) fear-like states in humans and primates (Gungor and Paré, 2016;Shackman and Fox, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second, WS-US contingency was held constant, but WS duration was varied to test how US imminence affects AR learning. In Pavlovian studies, reducing US certainty or imminence appears to promote anxiety over fear; freezing reactions are diminished and more flexible antipredator strategies increase (Blanchard et al, 1989;Cain et al, 2005;Goode et al, 2019;Helmstetter and Fanselow, 1993;Kim and Jung, 2018;Mobbs et al, 2007;Rescorla, 1968;Waddell et al, 2006). Also, lesions that impair freezing rescue ARs in poor avoiders, suggesting that freezing reactions interfere with avoidance (Choi et al, 2010;Lazaro-Munoz et al, 2010;Moscarello and LeDoux, 2013).…”
mentioning
confidence: 99%